Assessing the role of spin noise in the precision timing of millisecond pulsars - Shannon, Ryan; Cordes, J. (Institute of Physics Publishing, 2010)
We investigate rotational spin noise (referred to as timing noise) in non-accreting pulsars: millisecond pulsars, canonical pulsars, and magnetars. Particular attention is placed on quantifying the strength and non-stationarity of timing noise in millisecond pulsars because the long-term stability of these objects is required to detect nanohertz gravitational radiation. We show that a single scaling law is sufficient to characterize timing noise in millisecond and canonical pulsars while the same scaling law underestimates the levels of timing noise in magnetars. The scaling law, along with a detailed study of the millisecond pulsar B1937+21, leads us to conclude that timing noise is latent in most millisecond pulsars and will be measurable in many objects when better arrival time estimates are obtained over long data spans. The sensitivity of a pulsar timing array to gravitational radiation is strongly affected by any timing noise. We conclude that detection of proposed gravitational wave backgrounds will require the analysis of more objects than previously suggested over data spans that depend on the spectra of both the gravitational wave background and of the timing noise. It is imperative to find additional millisecond pulsars in current and future surveys in order to reduce the effects of timing noise. © 2010. The American Astronomical Society. All rights reserved.